Pengenalan Pesantren dan Literasi Islami melalui Pelatihan Menulis Pegon untuk Santri TPQ Desa Made - Hidayat, Rohmat; Mutrofin, Akmam; Wafa, M. Aliyul; Mubarok, Ahmad Dahril; Fahmi, M. Fatkhur Rizal; Naufal A., Muhammad Ibnu; Solikhah, Nanda Fitrotus; Sari, Dewi Ayu Puspita (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Pegon serves as an Islamic literacy bridge, facilitating the integration of local culture and Islamic teachings. It preserves the local language while strengthening religious values within the community. The objective of this community service program is to introduce Islamic literacy to students at the TPQ in Made Village through training in Pegon script writing. It is hoped that this will increase their understanding of Islamic cultural heritage and develop literacy skills that focus on Islamic values. The methodology employed is Participatory Action Research (PAR), which is oriented towards community empowerment through the active participation of students from three TPQs in Made Village: TPQ Al-Fathani, TPQ Al-Ikhlas, and TPQ Nurul Iman. The training proved effective in enhancing the students' comprehension of the Pegon script and facilitating a more profound understanding of Islamic literacy. The students' enthusiasm was palpable during the training sessions, particularly during the question-and-answer periods and the interactive discussions, during which they proactively sought clarification and demonstrated a keen interest in practicing writing in the Pegon script. Furthermore, the TPQ teachers provided comprehensive assistance, which was crucial to the successful implementation of the activities. This support fostered a collaborative learning environment and contributed to the program's success. Reviving Pegon literacy through this type of training is crucial. It not only preserves the cultural heritage of Islam in the archipelago but also enhances religious literacy within a pertinent local context. The program significantly reinforces the identity of Muslims in Indonesia by ensuring the maintenance and advancement of religious and cultural values through Pegon literacy in Islamic educational settings.